SEASONAL GROWTH AND GRAZING BEHAVIOUR OF DJALLONKÉ SHEEP RAISED IN ECOSYSTEMS OF IRRIGATED AND RAIN FED LANDSCAPES OF THE GUINEA SAVANNA ZONE OF GHANA - Bawah, J.; Ansah, T.; Dittoh, S.; Dei, H. K; Karbo, N. (UDS International Journal of Development, 2023)
The study was conducted in the Nabdam, Bawku-West, Kasena-Nankana districts of the Upper East Region, and the Kumbungu district in the Northern Region of Ghana. Twelve (12) ecosystems within four landscapes were selected for this research in the rainy (May- October) and dry (November-April) seasons. Twelve (12) grazing sites were purposively selected and a two-step sampling approach was used in the selection of sampling points within the grazing lands. The grazing behaviour of 36 Djallonké rams (weighing ≈13kg) was observed in the 12 ecosystems. Generally, Feeding, Watering and Walking by the rams were affected by the season in both landscapes. The rams spent less time for watering (11% dry season vs, 8 % wet season) and walking (40% dry season vs. 30% wet season) but high percentage of time on feeding (45% wet season vs. 31% dry season) during the wet season in the rain-fed landscape. Forage analysis were carried out to determine the effect of ecosystem and season on the growth performance of the rams in the landscapes. Season had a significant effect on all the growth parameters. Higher final weight (16.56 vs 15.08 kg), final weight gain (3.27 vs 2.28 kg) and average daily weight gain (54.5 vs 38.1 g) was observed in the wet season than in the dry season in the irrigated landscape. In the rain fed landscape, the effects of the ecosystem and season interaction was not significant, there was however a significant effect of season on the growth parameters. Higher final weight gain (2.8 vs 2.3 kg) and average daily weight gain (46.9 vs 39.4 g) was recorded in the wet season than in the dry season in the rain-fed landscape for the rams. The two-way interaction effect of ecosystem and season was not significant for any of the nutritional parameters in the irrigated landscapes. With the exception of dry matter (DM) which recorded higher values in the dry season, the main effect of season was significant with the wet season recording higher crude protein (CP) than the dry season in both rain fed and irrigated landscape. Keywords: Seasons, Growth, Behaviour, Djallonké Rams, Irrigated, Rain-fed